Designing An Information Security Framework For The Indonesia Water Industry Sector - Hidayatul Muttaqin; Kalamullah Ramli (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The majority of Indonesia's water industry sectors have implemented smart water management systems as part of their business development, which has an indirect impact on enterprise information security. However, in general, water sector enterprises continue to place a low priority on information security, and the development of information system frameworks is based on generic norms employed by financial firms. There has been no research on information security frameworks especially built for water firms in Indonesia that use information security standards in the utilities sector. This article proposes a solution in the form of a new framework for Indonesian water firms that combines international information security requirements in the utilities sector with Indonesian government rules. This approach of development combines worldwide standards with national rules. The Cybersecurity Capability Maturity Model (C2M2) and ISO 27019 are two international standards commonly used by utility businesses globally. Government Regulation or Peraturan Pemerintah (PP) Number 71 of 2019 on the Implementation of Electronic Systems and Transactions is the relevant national regulation. The framework addresses information technology, telecommunications, and operational technology, with four approach categories: governance and ecosystem, protection, defense, and resilience. According to the research findings, the newly integrated framework can be applied and is worthy of recommendation. This framework also meets the standards for information security and can be used by Indonesian water corporations.